The Possible Worlds of Hypertext Fiction - Bell, A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
Written in hypertext and read from a computer, hypertext novels exist as a collection of textual fragments, which must be pieced together by the reader. The Possible Worlds of Hypertext Fiction offers a new critical theory tailored specifically for this burgeoning genre, providing a much needed body of criticism in a key area of new media fiction.
Keywords: Literature, Modern—20th century; Literature—Philosophy.; British literature; Twentieth-Century Literature; Literary Theory; British and Irish Literature